2019
DOI: 10.3389/fnagi.2019.00063
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Receptor 1 Blockage Limits Brain Damage and Improves Functional Outcome After Brain Injury in Aged Animals Despite Age-Dependent Reduction in AT1 Expression

Abstract: Traumatic brain injury (TBI) is a frequent pathology associated with poor neurological outcome in the aged population. We recently observed accelerated cerebral inflammation in aged mice in response to TBI. Candesartan is a potent specific inhibitor of angiotensin II receptor type 1 (AT1) which limits cerebral inflammation and brain damage in juvenile animals after experimental TBI. In the present study, we show significantly lower posttraumatic AT1 mRNA levels in aged (21 months) compared to young (2 months) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(55 citation statements)
references
References 69 publications
2
53
0
Order By: Relevance
“…Coronal brain tissue slices were cut at the level of the cortical impact and separated between the left and right hemispheres. Upper right quadrants containing the lesioned and the perilesional brain tissue were snap-frozen in liquid nitrogen, stored at − 80°C, and further processed for quantitative real-time PCR (qRT-PCR)-based gene expression analyses as described before [47,49]. Briefly, all assays were carried out in our laboratory by an investigator blind to group allocation.…”
Section: Gene Expression Analyses By Quantitative Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronal brain tissue slices were cut at the level of the cortical impact and separated between the left and right hemispheres. Upper right quadrants containing the lesioned and the perilesional brain tissue were snap-frozen in liquid nitrogen, stored at − 80°C, and further processed for quantitative real-time PCR (qRT-PCR)-based gene expression analyses as described before [47,49]. Briefly, all assays were carried out in our laboratory by an investigator blind to group allocation.…”
Section: Gene Expression Analyses By Quantitative Real-time Pcrmentioning
confidence: 99%
“…Briefly, all assays were carried out in our laboratory by an investigator blind to group allocation. Using specific oligonucleotide primer pairs and optimized temperature conditions for qPCR, values were normalized to the reference gene PPIA (cyclophilin A) and absolute quantification was performed using a target-specific standard curve of mRNA copies [49]. The expression data analysis was performed with the LightCycler Software,…”
Section: Gene Expression Analyses By Quantitative Real-time Pcrmentioning
confidence: 99%
“…The different microglial phenotypes have not been deeply studied, but at 1 dpi, the M1 phenotype and most of the M2a phenotype genes are highly upregulated compared with young adults, in contrast with the M2c phenotype genes, which are downregulated [ 210 ]. Another study reported the reduced expression of M2a genes in aged TBI at 1 dpi compared with young adults, but this ratio was reversed at 5 dpi [ 205 ].…”
Section: Post-traumatic Neuroinflammation and Its Consequences In Vivomentioning
confidence: 99%
“…Qualitatively, more infiltration by neutrophils and fewer by monocytes was observed [ 200 ]. Quantitatively, the recruitment process in aged mice is emphasized and subchronically exacerbated as more newly recruited leukocytes are present in their brains than in those of young adults from 1 to 7 dpi [ 200 , 203 , 205 , 209 ]. However, a study reported altered neuroimmune response with fewer leukocytes infiltrating myeloid cells and microglia at 1 and 7 dpi in aged TBI rats, compared with young adults [ 211 ].…”
Section: Post-traumatic Neuroinflammation and Its Consequences In Vivomentioning
confidence: 99%
See 1 more Smart Citation